2000
DOI: 10.3748/wjg.v6.i5.651
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation by nizatidine, a histamine H2-receptor antagonist, of duodenal HCO3-secretion in rats: relation to anti-cholinesterase activity

Abstract: AIM To examine whether nizatidine stimulates duodenal HCO 3 -secretion in rats by inhibiting AChE activity. METHODS Under pentobarbital anesthesia, a proximal duodenal loop was perfused with saline, and the HCO 3 -secretion was measured at pH 7.0 using a pH-stat method and by adding 10mM HCl. Nizatidine, neostigmine, carbachol or famotidine was administered i.v. as a single injection. RESULTSIntravenous administration of nizatidine (3 -30mg/kg) dose-dependently increased duodenal HCO 3 -secretion, and the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Seto et al have reported that acotiamide suppressed the gene expression of neuromedin U, a known stress‐related neuropeptide. Acotimaide and drugs with anticholinesterase activity have also reported to stimulate duodenal bicarbonate secretion in rat models . Considering previous studies and our data, acotiamide may act directly on the gut and also indirectly through the brain‐gut axis such as ghrelin in the central nervous system …”
Section: Introductionsupporting
confidence: 71%
“…Seto et al have reported that acotiamide suppressed the gene expression of neuromedin U, a known stress‐related neuropeptide. Acotimaide and drugs with anticholinesterase activity have also reported to stimulate duodenal bicarbonate secretion in rat models . Considering previous studies and our data, acotiamide may act directly on the gut and also indirectly through the brain‐gut axis such as ghrelin in the central nervous system …”
Section: Introductionsupporting
confidence: 71%
“…In those days, several prokinetic agents such as dopamine 2 receptor antagonist and 5HT 4 receptor agonist were developed, and after elucidation of the mechanism of their effect on gastrointestinal regulatory systems, the clinical use of these agents was permitted. The investigators had originally obtained the idea for developing acotiamide from the AChE inhibition effect of nizatidine (H 2 ‐receptor antagonist) . The chemical structure of acotiamide actually resembles that of nizatidine in part.…”
Section: Discussionmentioning
confidence: 99%
“…idea for developing acotiamide from the AChE inhibition effect of nizatidine (H 2 -receptor antagonist) [19][20][21][22]. The chemical structure of acotiamide actually resembles that of nizatidine in part.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of these drugs on the activity of gastroesophageal motility has not been fully investigated and there are conflicting data in the literature 37–47 . Ranitidine and nizatidine have been reported to have anticholinesterase activity and to increase acetylcholine concentration at the synapses of parasympathetic neurons 39,48 . Therefore, these drugs may increase gastrointestinal motor activity by stimulating parasympathetic tone.…”
Section: Discussionmentioning
confidence: 99%